Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.22678
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated connexin 43 in HER2-positive drug resistant breast cancer cells enhances proliferation and migration

Abstract: Connexin 43 (Cx43) is a gap junction protein whose function in the development of breast cancer and in breast cancer progression remains unclear. Evidence suggests that Cx43 (GJA1) mRNA and protein expression is altered in breast tumors. However, reports indicate both increased and decreased Cx43 levels in human breast cancer samples. Studies also suggest that loss of Cx43 regulated gap junction intercellular communication is a common feature of breast malignancies that potentially correlates with histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…A previous study using immunohistochemistry found no correlation between Cx43 protein level and patient outcome [ 44 ]. However, similar to our results, more recent studies using expression array-based survival curves found that a high GJA1 expression was associated with a better prognosis in ER -positive breast cancer tumors, while an opposite trend was observed in ER -negative tumors [ 33 ] and Her2e tumors [ 34 ]. The worse prognosis associated with GJA1 in Her2e tumors suggests that GJA1 function in breast cancer might not just be tissue- and stage-dependent, as suggested by others [ 11 , 17 ], but might also be subtype-dependent.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A previous study using immunohistochemistry found no correlation between Cx43 protein level and patient outcome [ 44 ]. However, similar to our results, more recent studies using expression array-based survival curves found that a high GJA1 expression was associated with a better prognosis in ER -positive breast cancer tumors, while an opposite trend was observed in ER -negative tumors [ 33 ] and Her2e tumors [ 34 ]. The worse prognosis associated with GJA1 in Her2e tumors suggests that GJA1 function in breast cancer might not just be tissue- and stage-dependent, as suggested by others [ 11 , 17 ], but might also be subtype-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…To gain further insight into the role of Cx43 in breast cancer, we analyzed how the level of GJA1 mRNA expression in each subtype was associated with outcome. Observations that Cx43 expression was associated with a worse prognostic in ER-negative [ 33 ] and Her2e [ 34 ] tumors have been previously reported using the web-based platform KMPlotter [ 35 ] while ER-positive tumors had a better prognosis [ 33 ]. Investigating further the results of BreastMark and KMPlotter Web platforms, survival analysis showed that pooled and luminal tumors with high levels of GJA1 mRNA were associated with a better prognostic (hazard ratio < 1), although results were not always statistically significant ( Figure 7 and Figure A7 a,b).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In the human breast, Cx43 is expressed in luminal epithelial and myoepithelial compartments, while the expression of Cx26 is restricted to the luminal epithelium [7,8]. Altered expression, localization, and function of Cxs have been reported in human breast cancer tissues and in cell lines [9,10,11,12,13,14,15,16] and have been associated with developmental defects in mouse models [17,18,19], suggesting that Cxs have developmental and tumor suppressive roles. Indeed, Cx43 is proposed as an independent prognostic factor in light of its positive correlation with improved disease outcome in breast cancer patients [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…During the process of gap junction reorganization the amount of Cx43 protein not organized in gap junctions is increased [26]. The described dynamic dysregulation of Cx43 is under control of HER2 receptors (also called ErbB receptors), the typical cell proliferation modulators in breast cancer [27]. By the use of advanced co-culture experiments in networks of two-dimensional silicon based microfluidics, it can be demonstrated that tumor organization, gap junction establishment, and intercellular compound transfer are anisotropic and non-random and reflect tumor progression signal spreading along spatial routes decorated with Cx43 containing structures like hemi-channels, gap junctions, connexons and tunneling nanotubes [28].…”
Section: Introductionmentioning
confidence: 99%